A biophysical study of the interactions of palladium(ii), platinum(ii) and gold(iii) complexes of aminopyridyl-2, 2′-bipyridine ligands with RNAs and other nucleic acid structures. Issue 3 (23rd December 2022) - Binacchi, Francesca; Elia, Cassandra; Cirri, Damiano; Van de Griend, Corjan; Zhou, Xue-Quan; Messori, Luigi; Bonnet, Sylvestre; Pratesi, Alessandro; Biver, Tarita
Abstract : Aminopyridyl-2, 2′-bipyridine metal complexes prefer double/triple-stranded RNAs over DNA binding; Au(iii )/Pd(ii ) species show intriguing binding features toward RNA four-way junctions. Abstract : Metal compounds form an attractive class of ligands for a variety of nucleic acids. Five metal complexes bearing aminopyridyl-2, 2′-bipyridine tetradentate ligands and possessing a quasi-planar geometry were challenged toward different types of nucleic acid molecules including RNA polynucleotides in the duplex or triplex form, an RNA Holliday four-way junction, natural double helix DNA and a DNA G-quadruplex. The binding process was monitored comparatively using different spectroscopic and melting methods. The binding preferences that emerge from our analysis are discussed in relation to the structural features of the metal complexes.